Polyimide lithium ion battery separator and preparation method and application thereof

By introducing PVP as a pore-forming agent into the droplet superspreading technology, the problem of poor pore connectivity in polyimide lithium-ion battery separators was solved, realizing a three-dimensional interconnected sponge pore structure and improving the battery performance and safety of lithium-ion batteries.

CN121355517BActive Publication Date: 2026-05-15WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511467464.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-14
Publication Date
2026-05-15
Estimated Expiration
2045-10-14

AI Technical Summary

Technical Problem

Existing droplet superspreading technology has resulted in polyimide lithium-ion battery separators with mostly closed pores and poor connectivity, leading to high ion transport impedance and limiting battery performance.

Method used

By introducing the pore-forming agent PVP into the polyamic acid solution and controlling the phase exchange rate between the solvent and the coagulation bath, the formation of uniform and fine pores is promoted, and adjacent pores are connected to construct a three-dimensional interconnected sponge pore structure.

Benefits of technology

It significantly improves the pore connectivity of the separator, reduces lithium-ion transport impedance, supports rapid migration of the battery at high rates, and enhances battery cycle stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121355517B_ABST
    Figure CN121355517B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium battery separator, and particularly relates to a polyimide lithium ion battery separator, a preparation method and application thereof. The present application introduces a porogen into a new droplet super-spreading technology, successfully constructs a PI separator with a three-dimensional interconnected sponge pore structure. The present application effectively improves the problem of poor internal pore connectivity of the PI membrane prepared by the super-spreading technology, significantly reduces the lithium ion transmission impedance, can support the battery to realize fast lithium ion migration under high rate conditions, and meets the fast charging demand. In addition, the addition of the porogen inhibits the exchange rate between the solvent and the non-solvent, delays the phase separation process, thereby effectively inhibiting the formation of large pores, promoting the development of finer and more uniform pore structure, and further improving the cycle stability of the battery. Combined with the excellent high-temperature resistance of the polyimide material, the present application provides a new idea for developing high-safety and high-performance lithium ion battery separators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery separator technology, and in particular to a polyimide lithium-ion battery separator, its preparation method, and its application. Background Technology

[0002] In recent years, as lithium-ion batteries have developed towards smaller size and higher energy density, their safety issues have become increasingly prominent. Especially during rapid charge and discharge, effectively preventing or minimizing thermal runaway has become a core challenge in current battery safety management. Commercial polyolefin separators are prone to severe shrinkage at high temperatures, thus necessitating the development of next-generation separators that combine high thermal stability and high ionic conductivity to ensure efficient ion transport while achieving uniform lithium-ion flux, thereby suppressing lithium dendrite growth. Polyimide (PI) has become an ideal choice for high-safety lithium-ion battery separators due to its excellent thermal stability, chemical inertness, and mechanical strength.

[0003] Currently, traditional methods for preparing polyimide (PI) separators mainly include electrospinning and non-solvent-induced phase separation (NIPS). Electrospinning uses a high-voltage electric field to stretch a polymer solution into nanofibers, which are then randomly stacked to form a porous fibrous membrane. However, reported electrospun PI separators generally suffer from large pore sizes, wide pore size distributions, and low mechanical strength, making them prone to short circuits caused by lithium dendrite punctures. Therefore, inorganic composite materials or organic crosslinking methods are often needed to enhance their mechanical properties. For example, in their paper (In Situ Reinforcing: ZrO2-ArmoredHybrid Polyimide Separators for Advanced and Safe Lithium-Ion Batteries), Dong et al. increased the tensile strength of PI separators from 5.42 MPa to 39.24 MPa and enhanced their flame-retardant properties by constructing a dense ZrO2 nanolayer on the surface of PI nanofibers. Deng et al. (Cross-linked cellulose / carboxylated polyimidenanofiber separator for lithium-ion battery application) prepared cellulose acetate (CA) / PI nanofiber composite membranes using electrospinning technology. Alkaline hydrolysis exposed the carboxylic acid groups on the PI surface, which then crosslinked with CA via hydrogen bonds to form a three-dimensional interconnected structure, thereby improving the membrane's mechanical strength. Non-solvent-induced phase separation (NIPS) is another widely used porous membrane preparation technique. This method involves casting a polymer solution into a membrane and then immersing it in a non-solvent coagulation bath. Phase separation is induced by the exchange between the solvent and non-solvent, resulting in a porous structure. For example, Li et al., in their published paper (Novel Polyimide Separator Prepared with Two Porogens for Safe Lithium-Ion Batteries), successfully prepared nanoporous PI membranes by coating a polyamic acid (PAA) solution with an ethanol coagulation bath. However, the method of immersing the casting solution in the coagulation bath in this technique has significant limitations, making it difficult to precisely control the membrane pore structure, and the reproducibility of the preparation process is poor.

[0004] In the fabrication process of PI membranes, droplet superspreading, as an emerging technology in recent years, utilizes the surface tension difference between the polymer solution and the coagulation bath to achieve spontaneous and continuous spreading of the polymer solution on the surface of the coagulation bath. Simultaneously, solvent-non-solvent phase exchange occurs, resulting in nanoporous PI films. It has attracted considerable attention due to its efficient and controllable preparation of ultrathin homogeneous films. Huang et al., in their published paper (Superspreading-Based Fabrication of Thermostable Nanoporous Polyimide Membranes for High Safety Separators of Lithium-Ion Batteries), first used droplet superspreading technology to develop nanoporous PI membranes as high-safety separators for lithium-ion batteries. Later, Zhang et al. (patent CN 118507980 A) improved the superspreading technique for preparing PI membranes by introducing surfactants into the coagulation bath to delay the phase exchange process and suppress the formation of finger pores, successfully preparing PI membranes with a uniform sponge-like pore structure, exhibiting superior cycle stability. However, the thin films prepared by this method still suffer from insufficient pore connectivity. The large number of closed-pore structures leads to high ion transport impedance, which limits the overall performance of the battery. Summary of the Invention

[0005] In view of this, the present invention proposes a polyimide lithium-ion battery separator and its preparation method to solve the technical problem that the internal pores of the film are mostly closed and have poor connectivity when using droplet superspreading technology to prepare thin films. This avoids the high ion transport impedance caused by a large number of closed-pore structures, which limits the overall performance of the battery.

[0006] To address the aforementioned issues, this invention introduces a pore-forming agent, PVP (polyvinylpyrrolidone), into the superspreading system. By slowing down the diffusion rate of the solvent into the coagulation bath, the pore-forming agent promotes the formation of uniform and fine pores, connects adjacent pores, and opens closed pores, thereby successfully constructing a PI membrane with a three-dimensional interconnected sponge pore structure.

[0007] The technical solution of this invention is implemented as follows:

[0008] In a first aspect, the present invention provides a method for preparing a polyimide lithium-ion battery separator, comprising the following steps:

[0009] S1, Add a pore-forming agent to a polyamic acid (PAA) solution and stir until homogeneous to obtain a mixed solution;

[0010] S2, pour the mixed solution onto the surface of the coagulation bath, and after it spreads and solidifies on the surface of the coagulation bath, a wetted polyamic acid film can be obtained;

[0011] S3, the wetted polyamic acid film is transferred from the coagulation bath to water for immersion, and then removed and dried;

[0012] S4. The dried polyamic acid film is subjected to a step-by-step thermal imidization treatment to obtain a polyimide battery separator (PI film).

[0013] Based on the above technical solutions, preferably, in step S1, the pore-forming agent is polyvinylpyrrolidone (PVP).

[0014] During the spreading and phase exchange process, the role of PVP as a porogen can be divided into two stages: The first stage is the rapid phase exchange pore-forming stage. In this stage, the PVP porogen in the PAA solution undergoes phase exchange with the NMP solvent and water in the coagulation bath, promoting film solidification and the formation of pores. Since PVP dissolves along with the NMP solvent during film formation, the exchange rate between the solvent and the non-solvent (water) is suppressed, delaying the phase separation process and effectively inhibiting the formation of large-diameter pores, thus promoting the development of a finer pore structure. The second stage is the deep removal of PVP, which further removes residual PVP from the walls of adjacent pores. This deep removal of PVP penetrates adjacent pores and is a key stage for improving the connectivity of pores within the membrane. In this stage, the PVP porogen located at the pore walls dissolves deeply, allowing adjacent pores to interconnect and reducing the proportion of closed pores. This process mainly occurs in the subsequent water washing step to remove PVP.

[0015] Conventional technologies typically use PVP as a pore-forming agent as a template, forming pores through subsequent dissolution, which is a type of pore-forming process. This invention, however, optimizes the connectivity and uniformity of pores based on the existing porous structure through the aforementioned mechanism, thereby improving battery performance.

[0016] Based on the above technical solutions, preferably, the amount of the pore-forming agent is 2 to 6 wt% of the mass of the polyamic acid solution.

[0017] Adding only 2 wt% PVP can significantly improve battery performance without damaging the original uniform pore structure and is easy to remove the pore-forming agent. Conventional PVP pore-forming strategies usually require the addition of a higher content of pore-forming agent. A high content of hydrophilic pore-forming agent is not only difficult to disperse and affects the uniformity of the pore structure, but its complete removal is also more challenging.

[0018] Based on the above technical solution, it is further preferred that the amount of the pore-forming agent is 4 wt% of the mass of the polyamic acid solution.

[0019] Based on the above technical solutions, preferably, in step S1, the polyamic acid solution is obtained by adding 4,4'-diaminodiphenyl ether (ODA) and 4,4'-(hexafluoroisopropene) phthalic anhydride (6FDA) to 1-methyl-2-pyrrolidone (NMP) and stirring until homogeneous.

[0020] Based on the above technical solutions, preferably, the molar ratio of 4,4'-diaminodiphenyl ether to 4,4'-(hexafluoroisopropene)phthalic anhydride is 1:(0.8~1.2); more preferably, the molar ratio of 4,4'-diaminodiphenyl ether to 4,4'-(hexafluoroisopropene)phthalic anhydride is 1:1.

[0021] Based on the above technical solutions, preferably, in step S2, the coagulation bath is an aqueous solution of 1-methyl-2-pyrrolidone.

[0022] Based on the above technical solutions, preferably, the mass fraction of the 1-methyl-2-pyrrolidone aqueous solution is 35-45%; more preferably, the mass fraction of the 1-methyl-2-pyrrolidone aqueous solution is 40%.

[0023] Based on the above technical solutions, preferably, in step S3, the wetted PAA film is transferred from the coagulation bath to pure water for 1 hour to deeply dissolve the PVP pore-forming agent in the PAA film and remove the residual NMP solvent in the film, and then naturally dried at room temperature.

[0024] Based on the above technical solutions, preferably, in step S4, the stepwise thermal imidization treatment is to heat at 90~110℃, 190~210℃ and 290~310℃ for 50~70 min each.

[0025] Based on the above technical solutions, a further preferred method is to place the dried PAA film on a heating table for a step-by-step thermal imidization treatment: heating at 100℃, 200℃ and 300℃ for 1 h each to cause the polyamic acid molecular chain to undergo a cyclization and dehydration reaction, forming an imide ring structure, and finally obtaining a polyimide battery separator.

[0026] Secondly, a polyimide lithium-ion battery separator is provided, which is prepared by the above-described method for preparing a polyimide lithium-ion battery separator.

[0027] Thirdly, the application of polyimide lithium-ion battery separators as described above in lithium-ion batteries is provided.

[0028] The polyimide lithium-ion battery separator and its preparation method of the present invention have the following advantages over the prior art:

[0029] (1) The present invention successfully prepared a polyimide membrane with a three-dimensional interconnected sponge pore structure, which effectively improved the problem of poor internal pore connectivity of PI membrane prepared by super-spreading technology. At the same time, the membrane porosity and electrolyte wettability were improved, significantly reducing the lithium-ion transport impedance. It can support the rapid migration of lithium ions in the battery under 5C high rate conditions, meeting the fast charging application requirements.

[0030] (2) The introduction of pore-forming agent in the PI membrane preparation method of the present invention inhibits the exchange rate between solvent and non-solvent, delays the phase separation process, thereby effectively inhibiting the formation of macroporous structure, promoting the development of finer and more uniform pore structure, which is conducive to the uniform transport of lithium ions in the membrane channel, further enhancing the cycle stability of the battery and extending its cycle life.

[0031] (3) The PI film prepared by the PI film preparation method of the present invention fully retains the inherent high temperature resistance of polyimide material, which not only improves battery performance but also provides higher safety and reliability, effectively overcoming the thermal safety hazards of commercial polyolefin separators due to their low melting point. Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0033] Figure 1 This is a diagram illustrating the mechanism by which PVP, the pore-forming agent, affects the pore structure in the preparation method of this invention.

[0034] Figure 2 The images shown are SEM images of cross-sections of PI films prepared in the embodiments and comparative examples of the present invention. Images (a), (b), (c), (d), (e), and (f) represent SEM images of Comparative Example 1, Example 1, Example 2, Example 3, Comparative Example 2, and Comparative Example 3, respectively.

[0035] Figure 3 The figures shown are statistical diagrams of the cross-sectional pore structure and pore size of the PI films prepared in Example 2 and Comparative Example 1 of the present invention. Figures (a) and (b) represent the cross-sectional pore structure of the PI films in Example 2 and Comparative Example 1, respectively, and Figures (c) and (d) represent the statistical diagrams of the cross-sectional pore size of the PI films in Example 2 and Comparative Example 1, respectively.

[0036] Figure 4The figures shown are stress-strain curves of PI films prepared in the embodiments and comparative examples of the present invention. Figures (a), (b), (c), (d), (e), and (f) represent stress-strain curves of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.

[0037] Figure 5 This is a comparison diagram of the thermal dimensional stability of the PI film prepared in Example 2 and Comparative Example 1 of the present invention and the commercial PP separator;

[0038] Figure 6 Thermogravimetric curves of the PI membrane prepared in Example 2 and Comparative Example 1 of this invention and the commercial PP separator are shown.

[0039] Figure 7 This is a comparison diagram of the pore size distribution and gas flux of the PI membranes prepared in the embodiments and comparative examples of the present invention.

[0040] Figure 8 Impedance test diagrams of the PI membrane and commercial PP separator prepared in Example 2 and Comparative Example 1 of this invention;

[0041] Figure 9 The graphs show the ratio test results of the PI membrane prepared in Example 2 and Comparative Example 1 of this invention and the commercial PP separator.

[0042] Figure 10 The graphs show the 1C cycle performance of the PI membrane prepared in Example 2 and Comparative Example 1 of this invention and the commercial PP membrane.

[0043] Figure 11 The graphs show the 5C cycle performance of the PI membrane prepared in Example 2 and Comparative Example 1 of this invention and the commercial PP membrane. Detailed Implementation

[0044] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0045] The 4,4'-(hexafluoroisopropene)phthalic anhydride (6FDA) used in this invention was purchased from Aladdin Reagents. 4,4'-diaminodiphenyl ether (ODA) and 1-methyl-2-pyrrolidone (NMP) were both purchased from Sinopharm Reagents. Polyvinylpyrrolidone (PVP-K18) was purchased from Maclean's Reagents. The Aquaphor ultrapure water system was used to generate deionized water for the experiments. All reagents were used as indicated upon receipt without any additional purification.

[0046] Example 1

[0047] Take 20g of a prepared 12% PAA solution and add 0.4g of PVP porogen (equivalent to 2wt% of the PAA solution mass). Stir to fully dissolve and mix the PVP to obtain a PAA / PVP mixed solution. Then, mix NMP and water at a mass ratio of 40:60 to obtain a 40% NMP aqueous solution, which is used as a coagulation bath. Pour the PAA / PVP solution onto the surface of the coagulation bath, allowing it to spread and solidify fully, resulting in a wetted PAA film. Transfer the wetted PAA film from the coagulation bath to pure water and immerse it for 1 hour to deeply dissolve the PVP porogen and remove residual NMP solvent. Then, allow it to air dry at room temperature. Place the dried PAA film on a heating table for a stepped thermal imidization treatment: heat at 100℃, 200℃, and 300℃ for 1 hour each. h, causes the polyamic acid molecular chain to undergo a cyclization and dehydration reaction to form an imide ring structure, and finally obtains a polyimide battery separator; the separator is denoted as PI-2, indicating that the amount of PVP added is 2wt% of the mass of the PAA solution.

[0048] Example 2

[0049] The preparation method of this embodiment is basically the same as that of Example 1, except that: 20g of the synthesized 12% mass fraction PAA solution is taken and 0.8g of PVP pore-forming agent (equivalent to 4wt% of the mass of PAA solution) is added. The final polyimide battery separator is denoted as PI-4, which means that the amount of PVP added is 4wt% of the mass of PAA solution.

[0050] Example 3

[0051] The preparation method of this embodiment is basically the same as that of Example 1, except that: 20g of the synthesized 12% mass fraction PAA solution is taken and 1.2g of PVP pore-forming agent (equivalent to 6wt% of the mass of PAA solution) is added. The final polyimide battery separator is denoted as PI-6, which means that the amount of PVP added is 6wt% of the mass of PAA solution.

[0052] Comparative Example 1

[0053] The preparation method of this comparative example is basically the same as that of Example 1, except that: 20g of the synthesized 12% mass fraction PAA solution is taken, without adding PVP pore-forming agent, and shaken under the same conditions. The resulting polyimide battery separator is denoted as PI.

[0054] Comparative Example 2

[0055] The preparation method of this embodiment is basically the same as that of Example 1, except that: 20g of the synthesized 12% mass fraction PAA solution is taken and 1.6g of PVP pore-forming agent (equivalent to 8wt% of the mass of PAA solution) is added. The final polyimide battery separator is denoted as PI-8, which means that the amount of PVP added is 8wt% of the mass of PAA solution.

[0056] Comparative Example 3

[0057] The preparation method of this embodiment is basically the same as that of Example 1, except that: 20g of the synthesized 12% mass fraction PAA solution is taken and 2g of PVP pore-forming agent (equivalent to 10wt% of the mass of PAA solution) is added. The final polyimide battery separator is denoted as PI-10, which means that the amount of PVP added is 10wt% of the mass of PAA solution.

[0058] Performance Tests and Results

[0059] Cross-sectional scanning electron microscope (SEM) images of the polyimide battery separators (PI films) prepared in the above embodiments and comparative examples are shown below. Figure 2 As shown, the SEM images of Comparative Example 1, Example 1, Example 2, Example 3, Comparative Example 2, and Comparative Example 3 are respectively... Figure 2 Figures (a), (b), (c), (d), (e), and (f) in the figure show that, under the same preparation conditions, as the mass fraction of PVP porogen increases, the thickness of the resulting PI film remains relatively constant, but its structure gradually becomes more porous. Especially near the coagulation bath (the lower surface of the film in the figure), a large amount of PVP dissolves from the lower surface of the film and enters the coagulation bath, resulting in a more pronounced porous structure in this region.

[0060] The cross-sectional pore structure and pore size statistics of the PI films prepared in Example 2 and Comparative Example 1 are shown in the figure below. Figure 3 As shown. Figure 3 Figures (a) and (b) show the cross-sectional pore structures of the PI films in Example 2 and Comparative Example 1, respectively; figures (c) and (d) show the statistical diagrams of the cross-sectional pore sizes of the PI films in Example 2 and Comparative Example 1, respectively. Figure 3 It is evident that the addition of PVP porogen results in a denser pore distribution across the PI membrane cross-section, with a significantly reduced pore size and improved uniformity. This is because the PVP porogen dissolves along with the NMP solvent during film formation, inhibiting the exchange rate between the solvent and non-solvent (water), thus slowing down the phase separation process. Consequently, it effectively suppresses the formation of large-diameter pores and promotes the development of a finer pore structure.

[0061] The PI film prepared in the embodiments and comparative examples of the present invention, as well as the commercial PP film, were tested using conventional tensile strength, high temperature resistance, and characteristic weight loss temperature testing methods. The results are shown in Table 1.

[0062] Table 1

[0063]

[0064] In addition, the stress-strain curves of the PI films prepared in the examples and comparative examples were tested, and the results are as follows: Figure 4 As shown, Figure 4 Figures (a), (b), (c), (d), (e), and (f) in the figure represent the stress-strain curves of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.

[0065] Combining the data in Table 1 and Figure 4 It can be seen that, compared with the pure PI membrane (Comparative Example 1), the tensile stress of the membrane after adding PVP porogen first increases and then decreases with the increase of PVP addition. This is because the more compact pore structure formed by the introduction of an appropriate amount of PVP helps to distribute stress evenly, thereby improving mechanical strength; however, when the PVP content is too high, it will lead to an overly loose membrane structure, which will cause a decrease in strength.

[0066] The PI films prepared in Example 2 and Comparative Example 1, as well as the commercial PP separator, were placed on a heating stage and treated for 30 min at different temperature gradients (25℃, 80℃, 120℃, 160℃, 200℃, and 300℃) respectively. Thermal dimensional stability tests were then performed, and the results are as follows: Figure 5 As shown. (Combined with Table 1 and...) Figure 5 As can be seen, the commercial PP membrane shrinks significantly at 160°C and loses its structural stability; while the PI membranes prepared in Example 2 and Comparative Example 1 still maintain their complete dimensional shape at a high temperature of 300°C, indicating that the polyimide membrane prepared by the present invention has excellent thermal dimensional stability.

[0067] Figure 6 Thermogravimetric curves of the PI membranes prepared in Example 2 and Comparative Example 1, compared with those of commercial PP separators. See Table 1 for reference. Figure 6 Thermogravimetric analysis data shows that commercial PP membranes experience a sharp decrease in mass and significant thermal degradation after 430℃; while the PI membranes prepared using the technical solution of this invention only begin to experience significant mass loss at around 520℃, and their thermal decomposition rate is much lower than that of commercial PP membranes, exhibiting superior thermal stability.

[0068] The performance of the PI membranes prepared in the embodiments and comparative examples of the present invention, as well as the commercial PP membranes, in terms of pore parameters, electrolyte contact angle, and absorption rate was tested using conventional methods. The results are shown in Table 2.

[0069] Table 2

[0070]

[0071] The pore size distribution and gas flux diagrams of the PI membranes prepared in the embodiments and comparative examples of this invention are shown below. Figure 7 As shown, in conjunction with Table 1 and Figure 7 As can be seen, compared with pure PI membrane (Comparative Example 1), the addition of PVP porogen resulted in a finer pore structure, a smaller average pore size, and a narrower pore size distribution, while significantly increasing the gas flux. This is mainly because the dissolution of the PVP porogen during film formation effectively promotes the interconnection of pore walls, significantly enhancing the connectivity of pores, thereby improving the gas transport performance in the membrane.

[0072] Using stainless steel sheets as positive and negative electrodes and LB-266 as the electrolyte, coin cells were assembled using the PI membranes prepared in Example 2 and Comparative Example 1, as well as a commercially available PP membrane. Electrochemical impedance spectroscopy (EIS) tests were then performed, and the results are shown below. Figure 8 As shown in the figure, the battery impedance is significantly reduced when using a PI membrane with added PVP porogen, indicating that the introduction of porogen enhances the pore connectivity of the membrane, which is beneficial for ion migration within the membrane.

[0073] Using lithium iron phosphate (LFP) as the positive electrode, lithium foil as the negative electrode, and LB-266 as the electrolyte, coin cells were assembled using the PI separator prepared in Example 2 and Comparative Example 1, as well as a commercial PP separator. Rate performance was tested at room temperature (approximately 25°C), and the results are as follows: Figure 9 As shown in the figure. The results show that the battery using pure PI membrane already showed signs of capacity instability at 1C rate; while the PI membrane prepared by adding a pore-forming agent can still maintain a relatively stable initial capacity at a high rate of 5C, and its performance is comparable to or even better than that of commercial PP membrane batteries. This indicates that the more interconnected three-dimensional pore structure in the membrane is conducive to the rapid migration of lithium ions and supports the stable operation of the battery at high rates.

[0074] The assembled coin cells were subjected to charge-discharge cycle tests at a 1C charge-discharge rate at room temperature (approximately 25°C) to compare battery cycle stability. The results are as follows: Figure 10 As shown in the figure. The results show that the PI membrane prepared by adding PVP porogen has better pore connectivity and more uniform pore size distribution, thus significantly improving the cycling stability at a lower 1C rate, and the capacity retention rate is still over 80% after 500 charge-discharge cycles.

[0075] The assembled button cells were subjected to a 5C high-rate charge-discharge cycle test at room temperature (approximately 25°C) to compare the battery cycle stability. The results are as follows: Figure 11As shown, the battery assembled using the pure PI film of Comparative Example 1 could not operate normally at this rate, while the battery assembled in Example 2 still maintained a capacity retention of 94.3% after 400 cycles at a high rate of 5C. This effectively solves the problem that PI separators prepared by conventional droplet superspreading technology cannot support high-rate operation of lithium-ion batteries.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a polyimide lithium-ion battery separator, characterized in that, Includes the following steps: S1, Add a pore-forming agent to the polyamic acid solution and stir until homogeneous to obtain a mixed solution; S2, pour the mixed solution onto the surface of the coagulation bath, and after it spreads and solidifies on the surface of the coagulation bath, a wetted polyamic acid film can be obtained; S3, the wetted polyamic acid film is transferred from the coagulation bath to water for immersion, and then removed and dried; S4, the dried polyamic acid film is subjected to a step-by-step thermal imidization treatment to obtain a polyimide battery separator. In step S1, the pore-forming agent is polyvinylpyrrolidone, and its amount is 2 to 6 wt% of the mass of polyamic acid.

2. The method for preparing the polyimide lithium-ion battery separator as described in claim 1, characterized in that: In step S1, the polyamic acid solution is obtained by adding 4,4'-diaminodiphenyl ether and 4,4'-(hexafluoroisopropene) phthalic anhydride to 1-methyl-2-pyrrolidone and stirring until homogeneous.

3. The method for preparing the polyimide lithium-ion battery separator as described in claim 2, characterized in that: The molar ratio of the 4,4'-diaminodiphenyl ether and the 4,4'-(hexafluoroisopropene) phthalic anhydride is 1:(0.8~1.2).

4. The method for preparing the polyimide lithium-ion battery separator as described in claim 1, characterized in that: In step S2, the coagulation bath is an aqueous solution of 1-methyl-2-pyrrolidone.

5. The method for preparing the polyimide lithium-ion battery separator as described in claim 4, characterized in that: The mass fraction of the 1-methyl-2-pyrrolidone aqueous solution is 35-45%.

6. The method for preparing the polyimide lithium-ion battery separator as described in claim 1, characterized in that: In step S4, the stepwise thermal imidization treatment involves heating at 90~110℃, 190~210℃, and 290~310℃ for 50~70 min each.

7. A polyimide lithium-ion battery separator, characterized in that: It is prepared by the method for preparing polyimide lithium-ion battery separator according to any one of claims 1 to 6.

8. The application of the polyimide lithium-ion battery separator as described in claim 7 in lithium-ion batteries.